Respuesta :

Answer:  3x -- 5 x + 9

Step-by-step explanation: = x (3--1) + (--5 + 9)

                                             = x (2) + 4

                                             = 2x + 4

                                  putting x =3

                                           = 2 (3) + 4

                                           = 6 + 4

                                           = 10

9514 1404 393

Answer:

   19x +15

Step-by-step explanation:

5(x+2x)+(3*5)+(4)(x)

= 5(3x) +15 +4x

= 15x +4x +15

= 19x +15